2017
DOI: 10.1021/acsami.7b14775
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Ceramic Magnetoelectric Composites with Tailored Interfaces for Enhanced Response

Abstract: Composite materials consisting of two dissimilar ferroic phases are an excellent alternative to single-phase multiferroics for a wide range of magnetoelectric technologies. In composites with strain-mediated magnetoelectric coupling the response is strongly dependent on the characteristics of the interface between the two mechanically coupled phases. Among the different material approaches considered, cofired ceramic composites offer improved reliability in applications and are more adequate for free-forming a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In the case of lead-based ceramics, PFM analyses of domain structures were performed in PbTiO 3based [68][69][70] [33] and Pb(Fe 1/2 Nb 1/2 )O 3 -based [80] ceramic samples. The domain structures in lead-based ceramic samples vary significantly, from typical macro-sized domains [33,49,56,68,69] in ferroelectrics to polar nano-domains (PNDs) in relaxors [33,53,71,72,74], which are often called labyrinth-type [71,72] or finger-print nanoscale domains [53] or nanoscale quasi-regular maze domains [53,74].…”
Section: (A) Lead-based Ceramicsmentioning
confidence: 99%
“…In the case of lead-based ceramics, PFM analyses of domain structures were performed in PbTiO 3based [68][69][70] [33] and Pb(Fe 1/2 Nb 1/2 )O 3 -based [80] ceramic samples. The domain structures in lead-based ceramic samples vary significantly, from typical macro-sized domains [33,49,56,68,69] in ferroelectrics to polar nano-domains (PNDs) in relaxors [33,53,71,72,74], which are often called labyrinth-type [71,72] or finger-print nanoscale domains [53] or nanoscale quasi-regular maze domains [53,74].…”
Section: (A) Lead-based Ceramicsmentioning
confidence: 99%
“…Maximum α 31 E values of 21, 24, and 8 mV·cm −1 ·Oe −1 were obtained in the ceramic composites spark plasma sintered at these temperatures [18]. Note that figures do not coincide with those reported in [18], for the piezoelectric thickness was used in that case to normalize the magnetoelectric response.…”
Section: Simulations Against Experimental Resultsmentioning
confidence: 85%
“…Actually piezoresponse force microscopy (PFM) studies of this specific interface have shown that grains attached to the NIFe 2 O 4 layers are piezoelectrically active as it is illustrated in the inset. Moreover, an in-depth recent study has demonstrated fully-functional interfaces [31]. Therefore, this mechanism is not responsible for the reduction of the response in the specific case under study.…”
Section: Simulations Against Experimental Resultsmentioning
confidence: 89%
See 2 more Smart Citations